The genetics of frontotemporal dementia - Hardy, John (Henry Stewart Talks, 2014)
Overall characteristics of FTD, Genes involved in frontotemporal dementia, Pathology of frontotemporal dementia, FTDP-17: 3R and 4R-tauopathies, FTLD-TDP subtypes, MAPT as the gene for FTD with tangles, The microtubule associated protein tau, Mutations affecting tau protein in FTD, PGRN mutations as a cause for FTD, A major locus for FTD and ALS on chromosome 9, Chromosome 3 dementia, Making sense of these genes